ANALISIS STRATEGI GURU MEMPERSIAPKAN SISWA MENGIKUTI ASESMEN NASIONAL DI SD NEGERI 4 BANDA ACEH - Putra, Muhammad Nazir; Idris, Tasnim (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
Minimum Competency Assessment to measure the ability to develop reasoning using the International system to be creative and innovative according to the XXII century. Furthermore, it requires teachers at State Elementary School 4 Banda Aceh to have various strategies for maximum results with the aim of knowing the teacher's strategy for preparing AKM, knowing the role of the class teacher and being able to find out the supporting and inhibiting factors in preparing for the implementation of AKM at SD Negeri 4 Banda Aceh. The research population was 2 class teachers with data collection through interviews and documentation. So, the results of the research were that teachers at SD Negeri 4 Banda Aceh prepared AKM using questions from the module. The existence of AKM books and discussions, support for learning media as well as tips and tricks in discussing questions, the availability of various books in the literacy corner in each class and frequent practice of questions from various book sources and reading in the form of stories as well as adjustments to all the subject matter tested and adjustments to learning with student characteristics in accordance with the evaluation of education report reports with the role of teachers providing various facilities and infrastructure with support programs for implementation and training with supporting methods with the availability of facilities and infrastructure that hinder literacy habits not being a priority, the environment does not support and teaching materials that integrate knowledge and AKM material is lacking